In Modern Operations, the Restraints of Modern Seams, Seams, and Problems Derived - qizi, Ganjiyeva Munisa Komil (American Journal of Biomedicine and Pharmacy, 2025)
Modern surgical procedures have undergone a dramatic evolution in recent decades, fueled by advancements in technology, materials science, and clinical methodology. Despite these achievements, challenges persist, particularly in the domain of surgical seams—an integral aspect of any operation. Surgical seams or sutures are essential for wound closure, tissue healing, and postoperative stability. However, they remain a common source of postoperative complications, including infection, dehiscence, adhesions, and chronic pain. This article provides a comprehensive analysis of the current techniques, materials, and problems associated with surgical seams. The paper highlights the limitations of traditional methods, the innovations in suture materials, the emergence of minimally invasive closures, and the development of absorbable and non-absorbable options. Clinical findings and research data are used to support a practical, evidence-based approach to selecting optimal suture strategies depending on surgical type and patient condition. Modern surgical techniques have dramatically transformed the landscape of operative care, with an emphasis on precision, minimal invasiveness, and accelerated healing. Among the core components of surgical success, the application and outcome of wound closure remain crucial determinants of patient recovery. Seam management—particularly the selection, application, and integration of suture materials—plays a pivotal role in post-operative success. Despite innovations in closure systems, recurring complications such as wound dehiscence, foreign body reactions, and suboptimal tissue integration persist. These issues are especially prevalent in high-risk surgical fields like cardiovascular, gastrointestinal, and orthopedic surgery. The evolution of surgical seams now involves not only mechanical function but also immunological and biochemical compatibility. As modern medicine progresses, attention is shifting from merely closing wounds to enhancing tissue interaction, bioactivity, and long-term integrity. Therefore, the systematic exploration of seam-related outcomes is essential for refining protocols and minimizing preventable complications.